Prevalence and multi-level factors associated with acute malnutrition among children aged 6–59 months from war affected communities of Tigray, Northern Ethiopia, 2021: a cross-sectional study - Gebretsadkan Gebremedhin Gebretsadik; Mahlet Abraha; Tedros Bereket; Ferehiwot Hailemariam; Freweini Gebrearegay; Tigist Hagos; Mizan Assefa; Kidanemaryam Berhe; Hadush Gebregziabher; Amaha Kahsay Adhanu; Mekonnen Haileselassie; Mulugeta Gebregziabher; et al. (Conflict and Health, 2023)
Abstract Background Armed conflicts greatly affect the health, nutrition, and food security of conflict affected settings particularly children. However, no empirical data exist regarding context specific factors contributing towards acute malnutrition in the war-torn Tigray, Ethiopia. Thus, this study aimed to identify individual and community level factors associated with acute malnutrition among children aged 6–59 months from armed conflict affected settings of Tigray, Ethiopia. Methods A community based cross-sectional study was conducted among 3,614 children aged 6–59 months in Tigray, from July 15 to Aug 15, 2021. Study participants were selected using a two-stage random sampling method. A structured questionnaire was used to collect data by interviewing mothers/caregivers. Mid upper arm circumference (MUAC) measurements were taken from upper left arm of the children using MUAC tapes. Multivariable multilevel logistic regression analysis was used to determine factors associated with acute malnutrition. Adjusted Odds ratio (AOR) with 95% CI were estimated to describe the strength of associations at p < 0.05. Results More than half (52.5%) of the sampled children were males in sex. Immediately after the first nine months into the conflict, the prevalence of severe, moderate, and global acute malnutrition was very high (5.1%, 21.8%, and 26.9%, respectively) in Tigray. The lowest and highest burden of child acute malnutrition was reported from Mekelle zone (13.3%) and Southeastern zone (36.7%), respectively. Individual-level factors such as older child age (AOR = 0.13, 95% CI: 0.10, 0.18), female child sex (AOR = 1.24, 95% CI 1.05, 1.480.95), Vitamin-A supplementation (AOR = 1.3, 95% CI: 1.05, 1.65), and history of diarrhea (AOR = 1.22, 95%CI: 1.02, 1.53) and community-level factors like unimproved drinking water source (AOR = 1.31, 95%CI: 1.08, 1.58), unimproved toilet facility (AOR = 1.24, 95% CI: 1.01, 1.52), and severe food insecurity (AOR = 1.55, 95% CI: 1.16. 2.07) were significantly associated with childhood acute malnutrition. Conclusions The burden of acute malnutrition is a severe public health problem in Tigray. To prevent the untimely suffering and death of children, regular nutrition screening, speedy, and appropriate referral of all malnourished children to nutritional services and large-scale humanitarian assistance including access to food; nutrition supplies; water, sanitation and hygiene supplies; and health care in a timely manner are required. In the prevailing armed conflict, these have been very difficult to achieve. Thus, immediate international intervention is needed.